Analisis Kelayakan Berjalan dan Faktor yang Memengaruhi Minat Berjalan Kaki di Jakarta - Kurniawati, Wahyuni (Jurnal Kebijakan Ekonomi, 2019)
Walking is the main mode of transportation for most people around the world and is a link from one mode of transportation to another. Pedestrian paths in Jakarta have not been able to provide comfort for pedestrians, meaning, it can be said that the sidewalks in Jakarta are not yet walkable and have not been filled with adequate facilities. Pedestrian facilities are measured using walkability. Walkability is included in accessibility that has a good economic impact, namely saving transportation costs, efficiency of land use, increasing property prices (residential), saving health costs, and economic development. The provision of pedestrian areas is not balanced compared to the procurement of other public infrastructure. The purpose of this study was to examine a person's walking intention in terms of socio-economic demographic factors and walking feasibility. These factors are thought to influence the perception of interest and preference for walking. This study used qualitative research methods with observation, questionnaire surveys, and pedestrians as well as using quantitative research methods with logistic regression analysis. The research was conducted on two roads, Jalan Jenderal Sudirman and Jalan Salemba Raya.